Liver transplantation in Acute-on-Chronic liver failure: Timing of transplantation and selection of patient population - Li, Xue; Zhang, Liang; Pu, Chunmei; Tang, Shanhong (Frontiers in Medicine, 2022)
Acute-on-Chronic liver failure (ACLF) is a clinical syndrome with high short-term mortality. Alcoholic ACLF is prevalent in European and American countries, while HBV related ACLF is more common in Asia-Pacific. Due to various etiology and pathogenesis in different continents, there is still a lack of a unified definition standard for ACLF. Currently, liver transplantation (LT) is the most effective treatment for liver failure. However, the shortage of liver sources is still a global problem, which seriously limits the clinical application of LT. Premature LT aggravates the shortage of liver resources to a certain extent, and too late may significantly increase the risk of complications and death. Therefore, this review reviews the current literature on LT in the treatment of ACLF and further discusses the challenges for ACLF patients, the timing of LT for ACLF, and the choice of the patient population.